Phenol Administration in Adolescents with Pilonidal Sinus is Effective and Related to High Patient Satisfaction Rates - Cem Karaali; Ali Sayan; Mustafa Emiroğlu; Mehmet Mert; Halit Batuhan Demir; İsmail Sert; Gökhan Köylüoğlu; Cengiz Aydın (Galenos Yayinevi, 2021)
Aim:Surgical methods are the most commonly used methods in the treatment of pilonidal sinus (PS) in the world but their recovery durations and return to work/school periods are long and the complication rates are high. Among minimally invasive methods, phenol therapy is frequently used in adults and successful results are reported. However, studies on phenol treatment in adolescents with PS are limited and their number of patients is small. Therefore, our study aims to determine whether 80% liquid phenol treatment can be used as first-line therapy in this age group.Materials and Methods:Primary and 9 between 14 and 19 years who were treated with 80% liquid phenol were included in this study. Patient data were obtained from their files retrospectively.Results:Of the patients, 69 (69.7%) were male and 30 (30.3%) were female. The mean age of the patients was 17.4±1.3 (minimum-maximum 14-19). The total recurrence and complication rates after phenol administration were 10.7% and 16.1%, respectively. According to the Likert-type questionnaire, the mean satisfaction rate was 8.7±1.7 (minimum-maximum 5-10).Conclusion:In our study, it has been shown that 80% liquid phenol treatment can be successfully applied in adolescents with PS with low recurrence and low major complication rates. In addition, we think that 80% liquid phenol treatment should be recommended as the first-line treatment option for both primary and postoperative recurrent adolescent patients with PS, as it ensures a quicker return to work/school and shows high satisfaction rates.